2019
DOI: 10.1186/s13024-019-0341-5
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type Cu/Zn-superoxide dismutase is misfolded in cerebrospinal fluid of sporadic amyotrophic lateral sclerosis

Abstract: BackgroundA subset of familial forms of amyotrophic lateral sclerosis (ALS) are caused by mutations in the gene coding Cu/Zn-superoxide dismutase (SOD1). Mutant SOD1 proteins are susceptible to misfolding and abnormally accumulated in spinal cord, which is most severely affected in ALS. It, however, remains quite controversial whether misfolding of wild-type SOD1 is involved in more prevalent sporadic ALS (sALS) cases without SOD1 mutations.MethodsCerebrospinal fluid (CSF) from patients including sALS as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 80 publications
5
50
0
Order By: Relevance
“…In the same study [97], ALS cases and neurological controls were characterized by slightly higher levels of SOD1 in CSF compared to those of healthy controls; however, the amount of SOD1 in CSF did not correlate with the severity of ALS. In CSF, significant fractions of SOD1 were also reported to be Nterminally truncated, but the amount of such truncated proteins did not differ between ALS and controls, suggesting little pathological roles of the truncated SOD1 in ALS [93,95]. In electrophoretic analysis of CSF, furthermore, neither SOD1-positive smears nor highmolecular-weight ladders were observed, indicating that detergent-resistant oligomers/aggregates were not evident in CSF of ALS [93,95].…”
Section: Misfolded Forms Of Sod1 In Cerebrospinal Fluid Of Alsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the same study [97], ALS cases and neurological controls were characterized by slightly higher levels of SOD1 in CSF compared to those of healthy controls; however, the amount of SOD1 in CSF did not correlate with the severity of ALS. In CSF, significant fractions of SOD1 were also reported to be Nterminally truncated, but the amount of such truncated proteins did not differ between ALS and controls, suggesting little pathological roles of the truncated SOD1 in ALS [93,95]. In electrophoretic analysis of CSF, furthermore, neither SOD1-positive smears nor highmolecular-weight ladders were observed, indicating that detergent-resistant oligomers/aggregates were not evident in CSF of ALS [93,95].…”
Section: Misfolded Forms Of Sod1 In Cerebrospinal Fluid Of Alsmentioning
confidence: 95%
“…Indeed, SOD1 is well known as a constituent of CSF, and amounts of SOD1 in CSF tended to increase as a function of age albeit with a low correlation coefficient (r 2 = 0.1~0.2) [92][93][94]. In most studies, total SOD1 levels in CSF appear to be not significantly different between ALS and neurological/non-neurological controls [92][93][94][95][96]. Alternatively, absolute levels of SOD1 in CSF were reported to show substantial variability among individuals but with little variability in each individual over time [97].…”
Section: Misfolded Forms Of Sod1 In Cerebrospinal Fluid Of Alsmentioning
confidence: 97%
See 1 more Smart Citation
“…SOD1 aggregates are present in both sporadic and familial ALS [30,31]. In addition, we found that most wild-type SOD1 proteins assume misfolded conformations in cerebrospinal uid of ALS patients regardless of SOD1 mutation status [32]. Thus, removal of SOD1 aggregates may be a potential therapeutic approach for ALS treatment.…”
Section: Introductionmentioning
confidence: 82%
“…Although the toxic prion-like propagation of mutant SOD1 is well recognized, human wild-type SOD1 may be an important substrate of TDP-43 seeding, because human wild-type SOD1 misfolding can propagate within cells and between cells in vitro (10,53), potentially resulting in gain-of-function cytotoxicity (30) and/or loss-of-function from diminished dismutase activity (54). Recent data has implicated a role for toxic forms of wild-type SOD1 secreted from sporadic ALS astrocytes (55) and detected in sporadic ALS CSF (56). Interestingly, it has been reported that misfolded mutant SOD1 acquires its own pathological interactome, including G3BP1, α-synuclein, and amyloid-β (17,57,58).…”
Section: Discussionmentioning
confidence: 99%